2013
DOI: 10.3844/ajisp.2013.88.93
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Driven Clinical Trials of Transfer Point Glucan #300 in Children With Chronic Respiratory Problems: Iii. Clinical Findings

Abstract: The role of glucan in stimulation of immune reactions has been studied for decades. In this report we focused on the effects of orally administered glucan in children with chronic respiratory problems. We measured the physical endurance using a 6MWT test and the levels of eNO in 50 children aged 8-12 years and evaluated the effects of 100 mg/d oral dose of glucan. We found significant improvements in physical indurance and exhaled nitric oxide in glucan-treated children. In addition, strong improvements in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…20% of the original level). It was found that the climatotherapy treatment together with speleotherapy, higher physical activity and improved nutrition resulted in significant medical improvements (Vetvicka et al, 2013a;2013b;2013c;Ostojic et al, 2013). As confirmed by other authors (Schuh, 1993), we showed that this improved regime leads to significant improvements of immune functions, lowering of the risk of infections and improvements in the state of current diseases such as respiratory problems or asthma bronchiale (Buka et al, 2006;Davis et al, 2004).…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…20% of the original level). It was found that the climatotherapy treatment together with speleotherapy, higher physical activity and improved nutrition resulted in significant medical improvements (Vetvicka et al, 2013a;2013b;2013c;Ostojic et al, 2013). As confirmed by other authors (Schuh, 1993), we showed that this improved regime leads to significant improvements of immune functions, lowering of the risk of infections and improvements in the state of current diseases such as respiratory problems or asthma bronchiale (Buka et al, 2006;Davis et al, 2004).…”
Section: Introductionsupporting
confidence: 70%
“…Nutritional intervention in the form of food supplementation, with nucleotides, micronutrients, bovine colostrum or glucans, in groups with increased physical challenge have become the main research approach of numerous laboratories (Ostojic et al, 2013;Davis et al, 2004;Gunzer et al, 2012;Ostojic and Obrenovic, 2012;Riera et al, 2013;Stier et al, 2014;Wolvers et al, 2006). It is the results of our quest for an increase of immune reactions not only in athletes, but also in clinical medicine (Ciacio et al, 2014) and in possible renovation of damaged mucosal immunity in children exposed to effects of environmental contaminants (Richter et al, 2014;Vetvicka et al, 2013a;2013b;2013c). Based on these trials, several commercial supplements appeared on the market, including Oral Impal from Nestle (Ciacio et al, 2014; Sublingual nucleotides, extract from germinated barley (Ostojic and Obrenovic, 2012) or Immunoactive from Bioiberica Spain (Wolvers et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophages and monocytes recognize β-glucans by various receptors present on their membrane (Vaclav et al, 2013). This recognition will result in the secretion of cytokines (Netea et al, 2008).…”
Section: Physicochemical Characterization Of β-Glucan Samplesmentioning
confidence: 99%